The Effects of Oil Prices on Macroeconomic Variables: Evidence from Azerbaijan - Mukhtarov, Shahriyar; Aliyev, Sannur; Zeynalov, Javid (International Journal of Energy Economics and Policy, 2019)
This study investigates the impact of oil prices on economic growth, export, inflation and exchange rate in Azerbaijan, employing Johansen cointegration and VECM methods to the data spanning from 2005:01 to 2019:01. The results from the Johansen cointegration method confirm the presence of a long-run relationship among the variables. Estimation results impulse-response and variance decomposition tests reveal that there is a positive and statistically significant impact of oil prices on economic growth, export and inflation for the Azerbaijani case. On the other hand, we find that oil prices have a negative impact on exchange rate. The results of this article will suggest to researchers and policy makers to comprehend the role of oil price shocks on economy in the case of Azerbaijan and other developing oil-rich countries. Keywords: Oil prices; economic growth; export; exchange rate; inflation; VECM; Azerbaijan JEL Classifications: E31, Q4 DOI: https://doi.org/10.32479/ijeep.8446